2011
DOI: 10.1007/s00024-011-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

Water and Chemical Properties of Hydrometeors Over Central European Mountains

Abstract: Atmospheric pollutants are transferred to the ground by the contribution of various types of hydrometeors. Because of the different techniques of measurement, comparative analyses between them are often neglected. Hence, the main goal is to compare water volume and chemistry of different types of hydrometeors and their role in both: water balance and pollutants deposition. The results of water input and atmospheric deposits chemistry at Szrenica Mt. during the period between 01 December 2008 and 28 February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…4c). Additionally, we showed that the largest wood parameter reductions in 1980-1990 occurred at sites with the highest frequency of severely acidified fog, connected with a low-lying cloud base of orographic origin (Błaś et al 2012;Godek et al 2012;Igawa et al 2015;Shimadera et al 2011;Yamaguchi et al 2015). This concerned sites at the westernmost and northwesternmost edges of the Sudetes and Moravian-Silesian Beskids, which were also well exposed to the advection of air from the W-NW sector (Group C).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…4c). Additionally, we showed that the largest wood parameter reductions in 1980-1990 occurred at sites with the highest frequency of severely acidified fog, connected with a low-lying cloud base of orographic origin (Błaś et al 2012;Godek et al 2012;Igawa et al 2015;Shimadera et al 2011;Yamaguchi et al 2015). This concerned sites at the westernmost and northwesternmost edges of the Sudetes and Moravian-Silesian Beskids, which were also well exposed to the advection of air from the W-NW sector (Group C).…”
Section: Discussionmentioning
confidence: 67%
“…This concerned sites at the westernmost and northwesternmost edges of the Sudetes and Moravian-Silesian Beskids, which were also well exposed to the advection of air from the W-NW sector (Group C). The location of these sites on the NW edge of the Sudetes, i.e., the side exposed to the prevailing circulation and largest pollutant sources, means they are characterized by the highest fog efficiency and pollutant deposition (Błaś et al 2002(Błaś et al , 2012Dore et al 1999;Godek et al 2012). The understanding of the reasons and the course of changes is facilitated by information on spatial diversity of the exposure time of the trees to heavily polluted atmospheric water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations